A content analysis of UPSEC text, High School Mathematics I student involvement word loading - Andrada, Corazon J.
U.P.S.E.C. aims and commits itself to the production of materials that are relevant and meaningful to the lives of children. This research paper tried to solve the problem of sustainability through a content analysis of U.P.S.E.C. curriculum materials.